De l'intérêt des textes délaissés - Dalix, Anne-Sophie (2008)
Most of the tablets and the fragments from Ugarit were discovered in the spaces delimited by the ancient constructions (royal palace, private houses) and belonged to their archives. However, among these objects made in clay, some of them are not tablet and were excavated in private tombs. Two of them are particularly interesting and enable to interrogate about their function. Did they constitute a part of the funeral material?